Building cognitive applications with IBM Watson Services. conversation - Azraq, Ahmed (IBM redbooks., 2017)
Abstract The Building Cognitive Applications with IBM Watson Services series is a seven-volume collection that introduces IBM® Watson™ cognitive computing services. The series includes an overview of specific IBM Watson® services with their associated architectures and simple code examples. Each volume describes how you can use and implement these services in your applications through practical use cases. The series includes the following volumes: , SG24-8387 Volume 1 Getting Started , SG24-8394 Volume 2 Conversation , SG24-8393 Volume 3 Visual Recognition , SG24-8391 Volume 4 Natural Language Classifier , SG24-8392 Volume 5 Language Translator , SG24-8388 Volume 6 Speech to Text and Text to Speech , SG24-8398 Volume 7 Natural Language Understanding Whether you are a beginner or an experienced developer, this collection provides the information you need to start your research on Watson services. If your goal is to become more familiar with Watson in relation to your current environment, or if you are evaluating cognitive computing, this collection can serve as a powerful learning tool. This IBM Redbooks® publication, Volume 2, describes how the Watson Conversation service can be used to create chatbots and user agents that understand natural-language input and communicate with your users simulating a real human conversation. It introduces the concepts that you need to understand in order to use the Watson Conversation service. It provides examples of applications that integrate the Watson Conversation service with other IBM Bluemix® services, such as the IBM IoT Platform, Text to Speech, Speech to Text, and Weather Company® Data, to implement practical use cases. You can develop and deploy the sample applications by following along in a step-by-step approach and using provided code snippets. Alternatively, you can download an existing Git project to more quickly deploy the application.